PENGARUH STRATEGI SEGMENTASI PASAR, TARGET PASAR & POSISI PASAR TERHADAP CITRA TOKO : (Studi Kasus Kimi Chilli Branded) - Shandra Lemy Dewanti,; Muhamad Aditya Yulianto,; Unna Ria Safitri,; Hari Purwanto, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2025)
Marketing strategy is one way to win the competition in a sustainable superior manner for goods or services companies. Marketing strategy can be seen as one of the bases used in preparing company plans in the field of marketing. This research uses quantitative methods. The data collection technique in this study was carried out by observing and distributing questionnaires to buyers of Kimi Chilli Branded Stores. Based on the results of research testing on segmentation variables, it is known that the p value (sig) is 0.000 <0.05. Based on the test results on the target market variable, it is known that the p value (sig) is 0.927> 0.05. Based on research on the market position variable, the p value (sig) is 0.000 <0.05. 05. This shows that simultaneously market segmentation, target market & market position have a positive effect on the image of Kimi Chilli Branded Stores